(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
Amparo appeal núm. 4577-2019 is filed by several deputies of the People’s Parliamentary Group against the agreement of the Bureau of the Congress of Deputies of June 20, 2019 rejecting the request for reconsideration of a previous agreement, that of May 23, 2019, which declared that it was not appropriate to review the agreement of the President of the Congress of Deputies, of 21 May, which considered that the requirement of a promise or oath to comply with the Constitution had been fulfilled by all the deputies.